2020
DOI: 10.3389/fonc.2020.564785
|View full text |Cite
|
Sign up to set email alerts
|

SCAP Mediated GDF15-Induced Invasion and EMT of Esophageal Cancer

Abstract: Background: GDF15 is a potential biomarker for patients with esophageal cancer (EC). However, the mechanistic role of GDF15 in the invasion and metastasis of EC remains poorly understood. Methods: We determined the expression and function of GDF15 in esophageal cancer cells (ESCCs) and in patient tissue samples using western blotting, migration, and invasion assays, immunohistochemistry, Co-IP assays, and quantitative real-time-PCR. In addition, a pulmonary metastatic nude mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In addition, previous research has found a link between GDF15 and invasion in other cancers. 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research has found a link between GDF15 and invasion in other cancers. 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated GDF-15 has been strongly associated with metastasis in prostate, esophageal, hepatocellular, colorectal, pancreatic, gastric, and endometrial cancers [151]. Esophageal, breast, and colon cancer models show that GDF-15 correlates with the loss of E-cadherin and that the inhibition of GDF-15 expression decreases cell migration and invasion ability [70,152,153]. In contrast, in A549 lung cancer cells, overexpression of GDF-15 reduces cell growth and migration and decreases the spread of lung and bone metastases [154].…”
Section: Cancermentioning
confidence: 99%
“…Over the course of the past few years, it has been shown to participate in carcinogenesis and tumor progression. Previous studies have indicated that GDF15 expression is elevated in certain types of tumor, including non-small cell lung cancer (16), cervical cancer (17), liver cancer (18), head and neck cancer (19), esophageal cancer (20), and so on (21)(22)(23)(24). However, certain studies have suggested that GDF15 may have a tumor-suppressive activity in various types of cancer cells, or at different stages of tumor growth (25).…”
Section: Introductionmentioning
confidence: 99%